The Prognostic Importance of CD20+ B lymphocytes in Colorectal Cancer and the Relation to Other Immune Cell subsets - Sofia Edin (Nature Portfolio, 2019)
Abstract The anti-tumour immune response is critical to patient prognosis in colorectal cancer (CRC). The aim of this study was to investigate infiltration of B lymphocytes into CRC tumours, and their clinical relevance, prognostic value and relation to other immune cell subsets. We used multiplexed immunohistochemistry and multispectral imaging to assay the amount of infiltrating CD20+ B lymphocytes along with infiltration of CD8+ cytotoxic T cells, FOXP3+ T regulatory cells, CD68+ macrophages and CD66b+ neutrophils, in 316 archival CRC tissue specimens. A higher density of infiltrating CD20+ B lymphocytes was associated with tumours of the right colon (P = 0.025) and of lower stages (P = 0.009). Furthermore, patients whose tumours were highly infiltrated by CD20+ B lymphocytes had a significantly improved disease-specific survival (HR = 0.45, 95% CI 0.28–0.73, P = 0.001), which remained significant in multivariable analysis. CD20+ B lymphocytes were highly and positively associated with CD8+ T lymphocytes (P < 0.001), and part of the prognostic role was found to be a cooperative effect between these lymphocyte subsets. Our results support a favourable prognostic value of tumour-infiltrating CD20+ B lymphocytes in CRC. Furthermore, a cooperative prognostic effect between CD20+ B lymphocytes and CD8+ T lymphocytes is suggested.